TINJAUAN MAQÂSID AL-SYARÎ’AH TERHADAP BUDAYA ORGANISASI DAN SUMBER DAYA MANUSIA DALAM KASUS MERGER BANK SYARIAH INDONESIA - Rukayah Rukayah (Universitas Muhammadiyah Surabaya, 2023)
Post-merger integration will definitely bring up new dynamics or problems in aspects of corporate culture and human resources. The clash of organizational culture conflicts is a critical factor that determines the success or failure of a merger process, therefore, the topic of organizational culture is an important one to study because, from here, the identity of a business organization will be revealed. Implementation of a good organizational culture will definitely be directly proportional to sharia compliance. Two years after the merger, Bank Sharia Indonesia has shown a positive trend towards the company's performance. The problem of this research can be formulated as follows: how is the strategy of Bank Sharia Indonesia in harmonizing organizational culture clashes during mergers, how is the implementation of sharia values (sharia compliance), and how is the review of maqâsid al-syarî'ah in both of these? This study aims to determine the strategy of Bank Sharia Indonesia in harmonizing organizational culture clashes that arise during a merger and how it is implemented in adherence to sharia values. The method used in this research is descriptive-qualitative with a case study approach. The results of this study found BSI strategies for harmonizing organizational culture. First, the BSI founder created the